2012
DOI: 10.1161/circulationaha.112.092312
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiography Screening for Rheumatic Heart Disease in Ugandan Schoolchildren

Abstract: Background— Historically, sub-Saharan Africa has had the highest prevalence rates of clinically detected rheumatic heart disease (RHD). Echocardiography-based screening improves detection of RHD in endemic regions. The newest screening guidelines (2006 World Health Organization/National Institutes of Health) have been tested across India and the Pacific Islands, but application in sub-Saharan Africa has, thus far, been limited to Mozambique. We used these guidelines to determine RHD prevalence in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
181
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 232 publications
(208 citation statements)
references
References 15 publications
(14 reference statements)
10
181
0
9
Order By: Relevance
“…(13) In February 2012, the World Heart Federation published the first evidence-based criteria for echocardiographic detection of RHD. (11) These guidelines were developed to resolve many of the current concerns with respect to the implementation of echocardiographic screening methods for RHD.…”
Section: Discussionmentioning
confidence: 99%
“…(13) In February 2012, the World Heart Federation published the first evidence-based criteria for echocardiographic detection of RHD. (11) These guidelines were developed to resolve many of the current concerns with respect to the implementation of echocardiographic screening methods for RHD.…”
Section: Discussionmentioning
confidence: 99%
“…Given the prevalence of congenital heart disease in rural populations, multiple international studies [8,11,13,14] Beaton et al [14,15] compared auscultation with protocolized echocardiography in sub-Saharan Africa. This study showed a significantly higher burden of disease than expected which was attributed to the poor sensitivity of auscultation for identification of such pathology.…”
Section: Discussionmentioning
confidence: 99%
“…The estimated prevalence of RF/RHD detected by echocardiography screening among children in the general population attending primary school is 1.5%. 1 About 50% of newly diagnosed rheumatic heart disease patients in Uganda present with complications, notably heart failure, pulmonary hypertension, infective endocarditis and atrial fibrillation.…”
Section: Introductionmentioning
confidence: 99%